Life and Limb : Perspectives on the American Civil War. - Seed, David; Kenny, Stephen C. (Stephen Christopher); Williams, Chris (Research and knowledge exchange impact officer) (Liverpool University Press, 2015)
A fascinating collection of primary sources on medical experiences in the US Civil War.